Asuhan Kebidanan Continuity of Care (CoC) dengan Bendungan ASI pada Ny. L.M. - Carvalho, Filomena de; Sofiyanti, Ida (Universitas Ngudi Waluyo, 2024)
The Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) are crucial indicators in developing country's health status, especially in developing countries like timorense. Despite a decrease, MMR and IMR in Timor Leste remain high, with the Sustainable Development Goals (SDGs) target of 70 per 100,000 live births for MMR and 12 per 1,000 live births for IMR. In Timorense , in 2015, there was an increase in MMR to 570 per 100,000 live births and IMR to 25 per 100,000 live births. The primary causes of MMR are pre-eclampsia/eclampsia and hemorrhage, while the main causes of IMR are low birth weight (LBW) and asphyxia. To address this issue, efforts are made to ensure that every mother and baby receives quality comprehensive midwifery care, including integrated antenatal care (ANC), delivery assistance by trained health personnel, postnatal care, and family planning services. Indonesia has implemented the Continuity of Care (CoC) program, which provides continuous care from pregnancy to family planning, proven effective in reducing mortality and morbidity rates. Based on this background, the author conducts a case study